2005
DOI: 10.1038/sj.leu.2403947
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-related leukemia: clinical characteristics and analysis of new molecular risk factors in 96 adult patients

Abstract: Therapy-related leukemia or myelodysplasia (t-leuk/MDS) is a serious problem that is increasing in frequency. We studied the clinical characteristics of 96 patients (pts) with a mean age of 48 years, and analyzed the molecular parameters that could predispose to t-leuk/MDS. Hematological malignancies were the most common primary (53%), followed by breast and ovarian cancer (30% combined). The mean latency until the development of t-AML was 45.5 months. Median survival was 10 months. Cytogenetics was abnormal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 47 publications
4
54
0
9
Order By: Relevance
“…Associations have been observed for glutathione S-transferase genes ( GSTM1 , GSTT1 and GSTP1 ), particularly among those with prior exposure to chemotherapeutic agents that are known GSTP1 substrates, 144 and for P-glycoprotein (encoded by MDR1 ), a cell membrane protein that impacts response to numerous chemotherapeutic agents. 145 A number of studies also have evaluated key DNA repair genes, including mismatch repair family members MLH1 146,147 and MSH2 , 148,149 RAD51 , 150 and XRCC3 . 151–153 Other polymorphisms in candidate genes from DNA repair pathways include ERCC2 of the nucleotide excision repair pathway 154 and two common functional p53-pathway variants.…”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…Associations have been observed for glutathione S-transferase genes ( GSTM1 , GSTT1 and GSTP1 ), particularly among those with prior exposure to chemotherapeutic agents that are known GSTP1 substrates, 144 and for P-glycoprotein (encoded by MDR1 ), a cell membrane protein that impacts response to numerous chemotherapeutic agents. 145 A number of studies also have evaluated key DNA repair genes, including mismatch repair family members MLH1 146,147 and MSH2 , 148,149 RAD51 , 150 and XRCC3 . 151–153 Other polymorphisms in candidate genes from DNA repair pathways include ERCC2 of the nucleotide excision repair pathway 154 and two common functional p53-pathway variants.…”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…8 Cytogenetically low-risk sAML patients were excluded, as they accounted for only n ¼ 4. Patients aged p60 years received intravenous double-induction chemotherapy containing cytosine arabinoside (100 mg/m 2 , days 1-8), mitoxantrone (10 mg/m 2 , days [4][5][6][7][8] and etoposide (100 mg/m 2 , days 4-8) ( ¼ MAV) in the first induction and cytosine arabinoside (2 Â 1000 mg/m 2 , days 1-5) and m-AMSA (100 mg/m 2 , days 1-5) ( ¼ MAMAC) during the second induction therapy. Patients with intermediate cytogenetic risk and an HLA-identical sibling donor were referred for allogeneic hematopoietic stem cell transplantation (HSCT).…”
Section: Methodsmentioning
confidence: 99%
“…5 Mutations induced by cytotoxic therapy, genetic predispositions that affect drug metabolism and DNA repair are implicated in the etiology of tAML. 6 The poor prognosis is based on cytogenetic abnormalities and the comorbidities of the underlying malignancy or acquired during previous cytotoxic therapy. Only 10-15% of the patients with de novo MDS or AML harbor the unbalanced aberrations 5q-/-5 or 7q-/-7, whereas in patients with tMDS or tAML, the incidence rises to 50-60%.…”
Section: Introductionmentioning
confidence: 99%
“…Worrillow et al (2003) demonstrated that the variant C allele was significantly over-represented in t-AML samples from patients who had previously undergone alkylating treatment with an odds ratio of 4AE02 when compared with controls. MSI The same patients have since been studied using different methodology and a lower degree of MSI was found (Rund et al, 2005). was also shown to occur in 13/34 of t-AML samples and two of these were homozygous for the MSH2 IVS12-6 variant (C) allele.…”
Section: Mismatch Repairmentioning
confidence: 99%